28 Can Comprehensive Geriatric Assessment be Achieved in the Emergency Department?. (6th February 2020) - Cheng, J; Ho, C; Honney, K; Wells, M; Wise, W; Ferguson, N; Bailey, S; May, H; Burridge, R
Abstract: Background: Our National Health Service is facing unprecedented challenges to accommodate our frailer healthcare users. The gold standard tool for the identification and management of frailty is the Comprehensive Geriatric Assessment (CGA) and has been shown to lead to better outcomes in terms of morbidity and mortality. Introduction: With a largely elderly demographic profile in the East of England, the Norfolk and Norwich University Hospital opened the first Older People's Emergency Department (OPED) in the UK in 2017. This work reviews the effectiveness of a geriatrician-led CGA in a dedicated OPED, which operates during daylight hours, compared to usual care in Accident & Emergency (A&E). Methods: 99 patients assessed in OPED and 99 patients assessed overnight in A&E during February 2019 were included in this retrospective study. Electronic case notes for each patient were reviewed by the authors and results were expressed as percentages. Results: OPED outperformed A&E in all components of the CGA; strongest areas included assessing for pain, falls risk and activities of daily living. Both departments performed well in reviewing medications and assessing for safeguarding concerns. Areas for improvement include assessing for mood disorders, sensory impairment, discussing Do Not Attempt Cardiopulmonary Resuscitation status, and end of life care plans. The average length of stay of OPED patients was only 7.3 days compared to 8.7 days in A&E, and 89% of OPED patients were discharged back to their usual residences compared to 87% in A&E. Conclusions: The improved CGA process in OPED has led to better outcomes, notably through a reduction in the average length of inpatient stay. Nevertheless, certain components of the CGA still require improvement. Further examination is needed to assess long-term mortality to support the use of CGA in the emergency setting.